Perancangan Aplikasi Pencarian Fasilitas Kesehatan ‘Find Medical’ dengan Menggunakan Metode Haversine dan Algoritma Dijkstra - Elrico Tanto Jaya; Ade Maulana; Jefri Junifer Pangaribuan (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
Currently, technology is rapidly advancing, enabling communication to be done with anyone, anywhere. The sophistication of this technology can be utilized to address issues in various fields, particularly in the healthcare sector, as healthcare is one of the most influential aspects of human life. One common problem in the healthcare sector is the lack of evenly distributed information about healthcare services, leading to difficulties for individuals in finding suitable healthcare facilities. Therefore, this research aims to develop an application called "Find Medical" as a solution to facilitate the public in searching for healthcare services that meet their needs. In this study, the Haversine method and Dijkstra's algorithm are employed to recommend the nearest healthcare services based on the user's location. The research objectives are to design the "Find Medical" application and analyze the accuracy of the employed methods. The "Find Medical" application is developed using the Laravel framework. Based on the testing results, the majority of respondents agree that the application is effective in addressing the inefficient healthcare information retrieval system. Additionally, the Haversine formula and Dijkstra's algorithm implemented in the application provide accurate recommendations with a precision rate of 90%. Therefore, the "Find Medical" application can be an effective and efficient solution for individuals seeking appropriate healthcare services.